2010
DOI: 10.1103/physreve.81.046602
|View full text |Cite
|
Sign up to set email alerts
|

Rogue waves and rational solutions of the Hirota equation

Abstract: The Hirota equation is a modified nonlinear Schrödinger equation (NLSE) that takes into account higher-order dispersion and time-delay corrections to the cubic nonlinearity. In describing wave propagation in the ocean and optical fibers, it can be viewed as an approximation which is more accurate than the NLSE. We have modified the Darboux transformation technique to show how to construct the hierarchy of rational solutions of the Hirota equation. We present explicit forms for the two lower-order solutions. Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
292
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 469 publications
(299 citation statements)
references
References 30 publications
7
292
0
Order By: Relevance
“…Even in the presence of phase randomization inherent to the study of incoherent waves or chaotic states, various numerical works have shown the spontaneous emergence of coherent localized waves (even rational solutions of the NLSE) from a turbulent environment [7,[13][14][15]. Rogue waves are not just an offshoot of breather collisions, but other mechanisms depending on the physical system must be taken into account in the formation of rogue waves, including the statistical approach, when noise is present [16].…”
Section: Introductionmentioning
confidence: 99%
“…Even in the presence of phase randomization inherent to the study of incoherent waves or chaotic states, various numerical works have shown the spontaneous emergence of coherent localized waves (even rational solutions of the NLSE) from a turbulent environment [7,[13][14][15]. Rogue waves are not just an offshoot of breather collisions, but other mechanisms depending on the physical system must be taken into account in the formation of rogue waves, including the statistical approach, when noise is present [16].…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments have taken into account dissipative effects [11,15,16], included higher-order nonlinear terms [17][18][19], or considered the coupling between several fields [20][21][22][23][24][25]. The latter investigations have led to the discovery of intricate rogue wave structures that are generally unattainable in the scalar models.…”
mentioning
confidence: 99%
“…Similar breathers describe the dynamic of unstable backgrounds in different integrable models (see e.g. [32][33][34][35]), that allows to generalise our results.…”
Section: Discussionmentioning
confidence: 86%